Implementation of Islamic Religious Education in Higher Education - Anam, Syaiful; Robbaniyah, Qiyadah; Lina, Roidah; Widiyanto, Widiyanto (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to determine the Implementation of Islamic Religious Education in tertiary institutions, with the object of research in tertiary institutions under Majlis Atturot Al-islamy Foundation. Qualitative research methods with the type of field research, data collection by interviews, observation and documentation. Data analysis with triangulation. The result of this research is that reviving religious culture among lecturers and staff in tertiary institutions can be an important effort to develop positive religious, moral and ethical values in the academic environment. Some of the religious cultures that are built in tertiary institutions are, Ikhlash, responsible, disciplined, and trustworthy in carrying out tasks, appearance, simple and in accordance with Shari'at guidelines, have noble character and can be role models for their students in speaking, behaving and behave, maintain and establish brotherhood between ustadz, prioritize husnudzhon attitudes, improve and develop scientific quality, maintain and implement Islamic law, guard speech, must participate in activities set by the institution, be fair and wise in imposing sanctions on students. obey the leadership and institutional regulations as long as they do not conflict with the Shari'a.The programs that are running are: studying the Koran, weekly studies,Â  wearing sharia clothes.